Systems of Global Meaning in Atheists and Theists: Divergent World Beliefs, Sources of Meaning, and Values - Park, Crystal L. (Journal for the scientific study of religion, 2025)
To illuminate the often-reported higher levels of meaning in life by those who believe in God relative to atheists, we examined the extent to which their global meaning (i.e., the beliefs, goals, and values that underlie subjective sense of meaning in life) differed. Study 1 (undergraduate sample of 100 atheists and 447 theists) found that theists endorsed higher levels of beliefs reflecting a more meaningful world (e.g., goodness, control, justice) while atheists endorsed higher beliefs in randomness. Further, atheists found less meaning from almost every source examined (e.g., achievement, self-acceptance). Results of Study 2 (87 atheists and 164 theists in a national U.S. online sample) produced similar results and also found theists more strongly endorsed many values that can facilitate a sense of meaning (e.g., traditionalism, security). Collectively, these results identify multiple divergences in global meaning between atheists and theists that may account for atheists’ lower meaning in life.